Evaluation of periodontal parameters in kidney transplant patients using immunosuppressive medications: a cross-sectional study - Geórgia Pires dos Santos Menezes; Fernanda Suely Barros Dantas; Katarina Haluli Janô da Veiga Pessoa; Jefferson Jorge Morais de Souza; Jair Carneiro Leão; Alessandra de Albuquerque Tavares Carvalho (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT Objective: The aim of this study was to evaluate periodontal parameters in renal transplant patients compared to a control group, due to the possible interference caused by the use of immunosuppressive medication. Methods: This was a cross-sectional observational epidemiological study of 80 patients. The transplant patients consisted of 40 patients, in whom the plaque index, clinical probing depth, clinical attachment level, bleeding on probing and the presence of gingival hyperplasia were analyzed. The control group, made up of 40 patients, was assessed according to the same indices. Results: No statistically significant difference was found between the groups with regard to the presence of plaque (p = 0.279), bleeding (p = 0.262), severity (p = 0.707) and location (p = 0.949) of periodontitis, only in relation to the grade (p = 0.041), where grade C was more present in transplant patients, with transplant time being a contributing factor. The presence of hyperplasia (p = 0.021), the gingival bleeding index (p = 0.011) and the plaque index (p = 0.031) were significantly higher in patients taking Ciclosporin. transplant patients had rapidly progressing periodontitis. Conclusion: Increased gingival volume, bleeding and plaque index were more associated with Ciclosporin use.